2015
DOI: 10.4103/2249-4863.174298
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of hand hygiene in undergraduate medical, dental, and nursing students: A cross-sectional survey

Abstract: Background:Hand hygiene is of paramount importance for the prevention of healthcare associated infections and the spread of antimicrobial resistance. There is a need to explore the concept of hand hygiene among the cross-disciplinary undergraduate healthcare students.Aim:To evaluate and compare the knowledge of hand hygiene among medical, dental, and nursing undergraduate students.Materials and Methods:A cross-sectional survey was conducted among 84 medical, 74 dental, and 40 nursing undergraduate students in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 16 publications
(25 reference statements)
3
44
3
4
Order By: Relevance
“…The majority of students participating in this study had high knowledge and attitude (86 and 65.1% respectively) with nonsignificant differences between both studied groups as regards to knowledge and significant differences regarding attitude. These results are higher than those recorded in the study of Thakker and Jadhav 18 on 74 dental students in a tertiary care teaching institute in India, where the majority (70.27%) of their students had moderate knowledge, while in 25.67% of them the knowledge was low. The difference from the present study could be attributed to the different scale used for assessment of the results as they considered more than 75% as a good knowledge, 50 to 74% as moderate, and <50% as poor.…”
Section: Discussioncontrasting
confidence: 54%
“…The majority of students participating in this study had high knowledge and attitude (86 and 65.1% respectively) with nonsignificant differences between both studied groups as regards to knowledge and significant differences regarding attitude. These results are higher than those recorded in the study of Thakker and Jadhav 18 on 74 dental students in a tertiary care teaching institute in India, where the majority (70.27%) of their students had moderate knowledge, while in 25.67% of them the knowledge was low. The difference from the present study could be attributed to the different scale used for assessment of the results as they considered more than 75% as a good knowledge, 50 to 74% as moderate, and <50% as poor.…”
Section: Discussioncontrasting
confidence: 54%
“…Similarly, another study reported high scores on the baseline hand hygiene questionnaire (data were not shown) (14). While, Thakker & Jadhav, (2015) evaluated the knowledge regarding hand hygiene and documented an unsatisfactory level of knowledge (15). Less than 50% undergraduate participants knew that unhygienic hands of HCW were the main route of transmission of potential harmful germs while in our study 73.2 % knew it.…”
Section: Discussionmentioning
confidence: 99%
“…Thakker and Jadhav (2015) conducted a similar study to this and documented poor knowledge. Out of 40 nursing students, only 37.5% knew that unclean hands were the main route of transmission of potentially harmful germs (Thakker&Jadhav, 2015).…”
Section: Discussionmentioning
confidence: 99%